2020
DOI: 10.1515/jpm-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coronavirus 19 pandemic on maternal anxiety during pregnancy: a prospectic observational study

Abstract: AbstractObjectivesCoronavirus (COVID-19) is a new respiratory disease that is spreading widely throughout the world. The aim of this study was to evaluate the psychological impact of COVID-19 pandemic on pregnant women in Italy.MethodsWe considered 200 pregnancies atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
223
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(263 citation statements)
references
References 27 publications
18
223
0
3
Order By: Relevance
“…In this sense, other previous studies have also observed that HRQoL decreased as the pregnancy progressed and that this metric improved postpartum [ 65 , 66 ]. However, the decrease in HRQoL reported in this study may have been aggravated by the stress and anxiety produced by the situation of confinement itself [ 24 , 67 , 68 , 69 ]. In agreement with our results, some authors have also observed an increase in anxiety and depression levels during confinement in pregnant women [ 67 , 68 ] and in the immediate postpartum period [ 69 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this sense, other previous studies have also observed that HRQoL decreased as the pregnancy progressed and that this metric improved postpartum [ 65 , 66 ]. However, the decrease in HRQoL reported in this study may have been aggravated by the stress and anxiety produced by the situation of confinement itself [ 24 , 67 , 68 , 69 ]. In agreement with our results, some authors have also observed an increase in anxiety and depression levels during confinement in pregnant women [ 67 , 68 ] and in the immediate postpartum period [ 69 ].…”
Section: Discussionmentioning
confidence: 87%
“…However, the decrease in HRQoL reported in this study may have been aggravated by the stress and anxiety produced by the situation of confinement itself [ 24 , 67 , 68 , 69 ]. In agreement with our results, some authors have also observed an increase in anxiety and depression levels during confinement in pregnant women [ 67 , 68 ] and in the immediate postpartum period [ 69 ]. Wu et al analyzed the anxiety and depression of 4124 Chinese women during the outbreak of coronavirus.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Some participants discussed the challenges of discussing mood related concerns over the telephone. There is emerging evidence to suggest that pregnant women are experiencing significant anxiety during the pandemic [ 9 11 ]. Further local and national strategies should be considered by policy makers to help further support this group of women.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing a rebound and preventing imports from abroad are essential. During the initial stage or peak of the COVID-19 outbreak, studies from China [5,6], Turkey [7], Italy [8], Canada [9], and Israel [10] have found that the COVID-19 had adverse psychological impact on women during pregnancy, such as increasing anxiety and depression symptoms. Several studies reported the behavior responses of pregnant women during the COVID-19 epidemic, such as wearing masks, washing hands more frequently and stocking up behaviors [11][12][13].…”
Section: Introductionmentioning
confidence: 99%